Burn Ointment Promotes Cutaneous Wound Healing by Modulating the PI3K/AKT/mTOR Signaling Pathway - Gan, Dali; Su, Qiyuan; Su, Hanwen; Wu, Li; Chen, Jun; Han, Bing; Xiang, Meixian (Frontiers in Pharmacology, 2021)
Burn Ointment (BO) is a clinically useful medicine for the treatment of burns and scalds. However, there is not enough scientific evidence to report the effect of BO on wound healing and its analgesic and anti-inflammatory efficacy. The aim of this work was to evaluate the anti-inflammatory and analgesic efficacy of BO and to reveal the potential wound healing properties and related mechanisms of BO. In this work, the content of active ingredients of BO was determined by high performance liquid chromatography (HPLC). Two animal models of inflammation were used to study its anti-inflammatory activity, and a hot plate method was used to evaluate its analgesic effect. In addition, mouse incision and rat burn models were used to investigate the effect of BO on the anti-inflammatory and wound healing mechanisms. The results showed that BO was safe for topical application, and BO could significantly inhibit auricular swelling in mice and paw swelling in rats, and significantly prolong the latency period of paw licking in the hot plate experiment in mice. It can also accelerate wound healing and repair scars by promoting the formation of new epithelial tissues in rat burn models. In addition, BO significantly down-regulated the serum levels of TNF-α and significantly increased the serum levels of VEGF and TGF-β1. Also, BO promoted the expression of collagen I and increased the ratio in p-PI3K/PI3K, p-AKT/AKT, and p-mTOR/mTOR pathways. Our results demonstrate the safety and efficacy of BO and suggest that activation of the PI3K/AKT/mTOR signaling pathway may play an important role in the promotion of wound healing by BO.